The impact of environmental resource learning applied to geometry in education for power and citizenship - Roosevelt Barros Morales; Mara Cabanilla Guerra; Carlos Barros; Sunny Bores Froment (OmniaScience, 2018)
This article is based on education for power and citizenship and related educational and social problems, where the axis of the issue is the environmental resources applied to learning geometry. These have a great impact on the teaching process, as it is currently considered that education should be interactive with respect to the environment. In recent years, the educational system has been able to perceive that, in scientific areas such as geometry, students have been limited to the role of receivers of conceptual contents from texts and websites, leaving aside the interaction by the learner with the surrounding environment. Studies using surveys conducted based on a Likert scale and administered with questions in simple language that is easily understood by the respondents have shown us that if the utility of environmental resources can be successfully merged with scientific areas, the result is greater knowledge acquisition and interest among students, especially in the area of geometry. This proposal is based on a change in the current educational model, employing a more attractive design, in which young people achieve greater proximity to subject being studied.